Sperm whales Gulf of California 2007-2008-accessory - Irvine, Ladd M.; Mate, Bruce R.; Palacios, Daniel M.; Follett, Tomas M. (Movebank Data Repository, 2019)
Irvine L, Palacios DM, Urbán, Mate B (2017) Sperm whale dive behavior characteristics derived from intermediate-duration archival tag data. Ecology and Evolution 258: 291–16. doi:10.1002/ece3.3322 : Here, we describe the diving behavior of sperm whales (Physeter macrocephalus) using the Advanced Dive Behavior (ADB) tag, which records depth data at 1‐Hz resolution and GPS‐quality locations for over 1 month, before releasing from the whale for recovery. A total of 27 ADB tags were deployed on sperm whales in the central Gulf of California, Mexico, during spring 2007 and 2008, of which 10 were recovered for data download. Tracking durations of all tags ranged from 0 to 34.5 days (median = 2.3 days), and 0.6 to 26.6 days (median = 5.0 days) for recovered tags. Recovered tags recorded a median of 50.8 GPS‐quality locations and 42.6 dives per day. Dive summary metrics were generated for archived dives and were subsequently classified into six categories using hierarchical cluster analysis. A mean of 77% of archived dives per individual were one of four dive categories with median Maximum Dive Depth >290 m (V‐shaped, Mid‐water, Benthic, or Variable), likely associated with foraging. Median Maximum Dive Depth was <30 m for the other two categories (Short‐ and Long‐duration shallow dives), likely representing socializing or resting behavior. Most tagged whales remained near the tagging area during the tracking period, but one moved north of Isla Tiburón, where it appeared to regularly dive to, and travel along the seafloor. Three whales were tagged on the same day in 2007 and subsequently traveled in close proximity (<1 km) for 2 days. During this period, the depth and timing of their dives were not coordinated, suggesting they were foraging on a vertically heterogeneous prey field. The multiweek dive records produced by ADB tags enabled us to generate a robust characterization of the diving behavior, activity budget, and individual variation for an important predator of the mesopelagos over temporal and spatial scales not previously possible.